Benefits of cooperation with the local and wider social community - Bezina, Anamarija; Gall Borjan, Jasminka (Rethinking childhood II: child and space, 2026)
Cooperation with the local and wider community is extremely important for the quality of work in preschool institutions, as it involves active interaction with their environment. Most of today’s children grow up simultaneously in the family and in educational institutions, which points to cooperation as a much-needed component for improving the quality of work. Cooperation in the parent-educator relationship strengthens the educator in their work and strengthens the parent in their role. Their shared responsibility is to ensure the child’s upbringing and education while providing consistent support throughout their development. In addition to the aforementioned cooperation, cooperation with the local community is equally important, as it also represents the framework in which the learning process takes place, yielding numerous benefits for the child’s development. In an educational institution, the atmosphere should be stimulating for the independent learning of all participants, but also for joint reflection that creates a collaborative culture, which is necessary for the growth and development of the kindergarten as a children’s home. In order to provide support for the complete development of the child, interactions with the immediate and wider social community are also encouraged. They refer to new spatial, material, and social environments, in which the child learns experientially. This was demonstrated through the project “Safe Kindergarten” – emergency situations, which used the Croatian Red Cross (HCK) educational platform as a support system during implementation. The project was realised on several levels: at the institutional level, in the form of parent meetings, workshops and visits by parents to the group (firefighters and nurses) and Croatian Red Cross employees; and at the community level through visits to institutions of the local community such as the Trogir Fire Department, the City Society of the Red Cross of Trogir, the Museum and the City Library. Through this form of project-based learning, all participants became co-constructors of our project. The children’s interests and curiosity encouraged us to continue the project within the framework of cooperation with the Civil Protection Service (education) and Croatian Waters institution (workshops and presentations).